Building a solid foundation: advancing evidence synthesis in agri-food systems science - Ellssel, Pierre; Küstner, Georg; Kaczorowska-Dolowy, Magdalena; Vázquez, Eduardo; Di Bene, Claudia; Li, Honghong; Brizuela-Torres, Diego; Elangovan Vennila, Elansurya; Vicente-Vicente, José Luis; Avila-Ortega, Daniel Itzamna (Frontiers in Sustainable Food Systems, 2024)
Enhancing the reliability of literature reviews and evidence synthesis is crucial for advancing the transformation of agriculture and food (agri-food) systems as well as for informed decisions and policy making. In this perspective, we argue that evidence syntheses in the field of agri-food systems research often suffer from a suite of methodological limitations that substantially increase the risk of bias, i.e., publication and selection bias, resulting in unreliable and potentially flawed conclusions and, consequently, poor decisions (e.g., policy direction, investment, research foci). We assessed 926 articles from the Collaboration for Environmental Evidence Database of Evidence Reviews (CEEDER) and recent examples from agri-food systems research to support our reasoning. The analysis of articles indicates that 43% of evidence reviews have serious deficiencies (Red), 40% have deficiencies (Amber), 17% are acceptable (Green), and only about 1% meet the standards (Gold). To enhance the quality of evidence synthesis in agri-food science, review authors should use tried-and-tested methodologies and publish peer-reviewed a priori protocols. Training in evidence synthesis methods should be scaled, with universities playing a crucial role. It is the shared duty of research authors, training providers, supervisors, reviewers, and editors to ensure that rigorous and robust evidence syntheses are made available to decision-makers. We argue that all these actors should be cognizant of these common mistakes to avoid publishing unreliable syntheses. Only by thinking as a community can we ensure that reliable evidence is provided to support appropriate decision-making in agri-food systems science.